Materi Stand Up Comedy Sebagai Objek Perlindungan Hak Cipta di Indonesia - Fiqqi Pujamantra; Indah Parmitasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research discusses stand-up comedy material as an object of copyright protection in Indonesia. This type of research is empirical legal research, the approach method used is the statutory regulation approach, case approach and context approach. Source material consists of primary data from interviews and secondary data in the form of primary, secondary and tertiary legal materials. Material was collected through interviews, literature study and document study which was then analyzed using qualitative descriptive methods. The results of this research are, first, Stand up comedy material is a copyrighted work which can be said to fulfill the concept of a copyrighted work based on the Copyright Law and can be included in objects protected by Copyright. Second, the legal efforts that can be taken by comics in the event of a copyright defense are that the resolution can be carried out through alternative dispute resolution, arbitration, or authorized institutions, namely commercial courts, as regulated in Article 95 of Law Number 28 of 2014 concerning Copyright on the basis of take legal action because it violates copyright and is an unlawful act.